2007
DOI: 10.2320/matertrans.maw200723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hf Addition on Oxidation Properties of Pt-Ir Modified Aluminide Coating

Abstract: In the present study, the effect of Hf addition on oxidation kinetics of Pt-Ir modified aluminide coatings was investigated. Pt-15 at%Ir and Pt-15 at%Ir with trace amount of Hf films with 7$8 mm thick were deposited on a Ni-based single crystal superalloy TMS-82+ using magnetron sputtering, followed by a diffusion treatment and conventional Al pack cementation. While there were no significant microstructual differences observed in as aluminized specimens, cyclic oxidation test at 1423 K revealed clear advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the Ir-Pt alloys, where Ir is added as a solution-hardening element, improved mechanical properties have been obtained at high temperatures [1][2][3]. In recent years, these alloys have been intensively investigated as coating materials for Ni-based superalloys, and found to exhibit promising oxidation resistance at high temperatures [4][5][6][7][8][9]. In contrast, at lower temperatures good mechanical properties due to the miscibility gap [1] is expected.…”
Section: Introductionmentioning
confidence: 99%
“…In the Ir-Pt alloys, where Ir is added as a solution-hardening element, improved mechanical properties have been obtained at high temperatures [1][2][3]. In recent years, these alloys have been intensively investigated as coating materials for Ni-based superalloys, and found to exhibit promising oxidation resistance at high temperatures [4][5][6][7][8][9]. In contrast, at lower temperatures good mechanical properties due to the miscibility gap [1] is expected.…”
Section: Introductionmentioning
confidence: 99%
“…Voids have also been observed at the bond-coating/substrate interface [18][19][20][21]. Vialas and Monceau [19] and Haynes et al [22] attributed their formation to a Kirkendall effect, but without clear proof.…”
Section: Introductionmentioning
confidence: 99%
“…Vialas and Monceau [19] and Haynes et al [22] attributed their formation to a Kirkendall effect, but without clear proof. Yamaguchi et al [20] suggested that cyclic oxidation is an additional source for vacancy supersaturation. Stacy et al [23] considered that hydrogen dissolution in the material during the Pt electroplating process could be a cause of void formation.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] For further improvement in protection performances, application of Ir based alloys to the bond-coats has been proposed. [13][14][15][16][17][18][19] At the same time, a Re modified aluminide coating has been shown to exhibit notable performance as a diffusion barrier. [20] Despite such promising performances of Ir in structural and coating application fields, only limited information is available for atomic diffusivity in Ir based alloys.…”
Section: Introductionmentioning
confidence: 99%